Deriving Countermeasures to the Use of Housing, Land and Property Rights as a War-Financing Commodity. Issue 1 (1st November 2022) - Unruh, Jon
Efforts to thwart the trafficking of conflict commodities to finance wars constitute an ongoing endeavour. As specific approaches become effective for certain commodities, belligerent actors pursue new forms of exploitation. The trafficking of housing, land and property (HLP) rights in war zones has now reached a pervasiveness, lucrativeness and severity to warrant significant attention on the derivation of countermeasures. This article proposes a set of potential countermeasures to trafficking in HLP rights in war zones by examining five sets of possible mechanisms and how they would work: detection, transnational governance, local-level countermeasures, public messaging, and targeting non-state armed groups.